2010
DOI: 10.1123/ijsnem.20.6.447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low- and High-Glycemic-Index Meals on Metabolism and Performance During High-Intensity, Intermittent Exercise

Abstract: Consuming carbohydrate-rich meals before continuous endurance exercise improves performance, yet few studies have evaluated the ideal preexercise meal for high-intensity intermittent exercise, which is characteristic of many team sports. The authors' purpose was to investigate the effects of low- and high-glycemic-index (GI) meals on metabolism and performance during high-intensity, intermittent exercise. Sixteen male participants completed three 90-min high-intensity intermittent running trials in a single-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
79
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 48 publications
10
79
1
1
Order By: Relevance
“…The lack of effect of carbohydrate supplementation, with or without BCAA and arginine, on the performance of high-intensity intermittent exercise is in contrast to previous studies in which low muscle glycogen content contributed to the development of fatigue in such type of exercise [2,4,54,55]. Although muscle biopsy was not performed, the exercise protocol used in our study would significantly reduce the glycogen content in the working muscles.…”
Section: Discussioncontrasting
confidence: 68%
“…The lack of effect of carbohydrate supplementation, with or without BCAA and arginine, on the performance of high-intensity intermittent exercise is in contrast to previous studies in which low muscle glycogen content contributed to the development of fatigue in such type of exercise [2,4,54,55]. Although muscle biopsy was not performed, the exercise protocol used in our study would significantly reduce the glycogen content in the working muscles.…”
Section: Discussioncontrasting
confidence: 68%
“…Accordingly, in the present study, carbohydrates showed a positive impact on athletic performance during the endurance test (p = 0.001), similar with other experimental studies in cyclists [20,46]. However, regarding the speed test of 200m, the consumption of carbohydrates from our cyclists did not have any ergogenic benefit (p = 0.163), which is suggested by [13].…”
Section: Discussionsupporting
confidence: 90%
“…They observed that participants' run time was higher after intaking LGI foods than the mentioned time after HGI foods; and the end of the exercise, serum FFA concentrations were higher after LGI than HGI meal [11]. There are some studies in support of these beneficial effects [14,15], however several studies found no different effect in TTE of athletes [16,17,18]. A study by Jamurtas and colleagues showed that ingestion of foods with LGI or HGI at 30 minutes prior to one-hour cycling did not show any significant changes in TTE values [16].…”
Section: Introductionmentioning
confidence: 90%